(untitled) (RR Interdisciplinary Journal, 2023)
The utilization of maternal health care is one of the important factors in reducing the incidence of maternal mortality. Studies in Nepal and in developing countries shows that various demographic, socio-economic and economic factors are associated with ANC service utilization. The main objective of this study is to identify and examine socio-demographic and economic factors affecting antenatal healthcare service utilization in Nepal. This study used data from the Nepal Demographic and Health Survey 2016 and analyzed the data using logistic regression analysis. This research analyzes ANC (antenatal care) concerning dependent variables: age, birth order, religion, ethnicity, educational attainment, province, residence, and wealth indices. Maternal health has been receiving increased attention in the global health, development, and human rights agenda, representing a priority area for accelerating progress on the SDGs and sustaining the gains of the MDGs. Bivariate analysis was conducted for all variables, and some of them were statistically significant at the 5 percent significance level (since p < 0.05). The dichotomous use of modern maternal healthcare utilization, namely whether a woman utilized maternal health care or not, employed dichotomous logistic regression to determine which factors best explain and predict the outcome of maternal health care utilization during pregnancy. A positive estimated value indicates that the odds favor the event and the event is likely to occur, while a negative value indicates that the event is not likely to occur. ANC visits of women decrease with birth order. Based on empirical results, the major factors for ANC services were income, awareness, access to health care services, and birth order attended. The level of awareness among women about the utilization of maternal healthcare in the study area was low. Maternal healthcare service utilization differed across various components of maternity. It would be better to increase awareness about the utilization of modern maternal healthcare for mothers and improve access to healthcare services in their villages to minimize transportation costs and waiting times from the government’s side, thus increasing the utilization of maternal health care services in Nepal.